Competências individuais requeridas para trabalhadores das indústria 4.0 da região sudoeste do Paraná - Marko, Mariane (2021)
This study aims to identify the main competences that are needed by Industry 4.0 workers pointed out in the literature and by professionals who work with people management in companies located in the Southwest Region of Paraná. First, a systematic review of scientific articles in the international Scopus database and articles published by renowned organizations that study the subject competences required for workers in Industry 4.0 was carried out. Subsequently, the skills required of workers in Industry 4.0 were investigated in the perception of 16 professionals who work with people management. It was found that the social skills, considered of high importance for Industry 4.0 are: leadership; teamwork, knowledge transmission and communication and problem solving. Regarding the methodological competences, the following stood out: decision making; conflict resolution, investigation skills. Regarding personal skills, the following were considered to be of high importance: flexibility; adaptability and creativity. With regard to technical skills, the following were indicated as relevant: automation; software security; coding competence and process understanding. In the conception of two managers, the coding competence was evaluated as being of little relevance, which in turn differed from the literature. Finally, this study makes it possible to advance with knowledge about the skills that are important for the worker's performance in the context of Industry 4.0.